Effects of acute psychological stress measurement in sports – EGIG, an innovative method to state stress response objectively - Nagy, Arnold; Almási, Dóra; Balogh, László (Arena-Journal of Physical Activities, 2017)
The aim of this study is to find an objective way to measure the well-re- searched topic of the zone by stating that electrogatro-intestinography (EGIG) is able to monitor the athletes stress response through the gastric and intes- tinal motility. Methods: 15 healthy team- and motorsports athletes under- went a resting EGIG which took 40 minutes with an audio stimulus (AS) at halftime. Records were made by an Electrogastrographic Myograph System– developed by MDE Co. Ltd. Results (n=15): All subjects had valid EGIG records. There were significant responses to the AS in the stomach (p=0,000), small intestine (p=0,000) and great intestine (p=0,001) as well. There were no significant differences between the resting amplitudes prior to and following the AS. Conclusion: Stress response can be monitored by EGIG. The great intestine is the most sensitive on stress. The scales of optimal zones are ex- pected by monitoring stress-response of the GI during training and competi- tion compared with personal results